Perlindungan Hukum Terhadap Anak Korban Eksploitasi Seksual Melalui Media Video Call - Chasanah, Kania Amru (UM Purwokerto Press, 2024)
Children are the embryo of the birth of a new generation which is the successor to the ideals of the nation's struggle and human resources for national development. Children are national assets, the future of the nation and state in the future is in the hands of children now.